ANALISIS PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI SULAWESI TENGAH - Latjuba, Andi Murfiqien (Katalogis, 2017)
The problem of this research is How Licensing Services in the Department of Investment and Licensing Services One Stop Central Sulawesi Province. This research analyzed descriptively qualitative. The informant in this research that a number of seven people comprising employees licensing services and licensing applicants drawn by pusposive sampling techniques. Mechanical collection and retrieval of data consists of observations, interviews, and documentation. The theory used in view of service quality is the theory of Parasuraman et al. consisting of tangibles, reliability, responsiveness, assurance, and empathy. The results showed that the licensing service in the Department of Investment and Licensing Services One Stop Provincial Central Sulawesi, which consists of reliability, responsiveness, assurance, and empathy, shows the level of service quality is good because of all of these aspects, nothing is obstructing the quality of service licensing of society. While the aspect of tangibles and there are obstacles that the lack of service facilities in this case the lack of computer facilities and room service are inadequate.